Canva-based Smart Apps Creator Media to Enhance Comprehension Skills of Informational Text for Third-Grade Students - Al Haq, Ghaida Tsurayya; Sismulyasih SB, Nugraheti; Purwati, Panca Dewi (Universitas Pendidikan Ganesha, 2024)
Learning media, as a tool for delivering information from teachers to students, aims to facilitate the teaching and learning process in school. Smart Apps Creator is a software with several advantages for developing interactive learning media, one of which is with the assistance of Canva application as its online design application. This research aims to create Canva-based Smart Apps Creator media to enhance the ability to understand the content of information texts in third-grade elementary schools. The research method used is Research and Development (R&D) based on Sugiyono's research with the Borg & Gall development model modified into eight stages, namely: potential and problems, data collection, product design, design validation, design revision, product testing, product revision, and usage testing. This research utilizes data collection techniques through tests and non-tests. The data analysis techniques used include both qualitative and quantitative data analysis. The material expert validation result obtained a percentage of 90%, and the media expert validation obtained a percentage of 92%, both categorized as